Examining the effects of interorganizational learning on performance : a meta-analysis - Rajala, Anni (Emerald, 2018)
Purpose: Relationship learning is viewed as an important factor in enhancing competitiveness and an important determinant of profitability in relationships. Prior studies have acknowledged the positive effects of interorganizational learning on performance, but the performance measures applied have varied. The purpose of this study is to examine the relationship between interorganizational learning and different types of performance. The paper also goes beyond direct effects by investigating the moderating effects of different research designs. Design/methodology/approach: This paper applies a meta-analytic approach to systematically analyze 21 independent studies (N = 4,618) to reveal the relationship between interorganizational learning and performance. Findings: The findings indicate that interorganizational learning is an important predictor of performance, and that the effects of interorganizational learning on performance differ in magnitude under different research conditions. Research limitations/implications: The paper focuses on interorganizational learning, and during the data collection, some related topics were excluded from the data search to retain the focus on learning. Practical implications: The study evinces the breadth of the field of interorganizational learning and how different research designs affect research results. Moreover, this meta-analysis indicates the need for greater clarity when defining the concepts used in studies and for definitions of the concepts applied in the field of interorganizational learning to be unified. Originality/value: This study is the first to meta-analytically synthesize literature on interorganizational learning. It also illuminates new perspectives for future studies within this field.
Keywords: interorganizational learning; relationship learning; performance; meta-analysis; fi=Johtaminen ja organisaatiot|en=Management and Organization|